Peran Guru Kelas Dalam Menumbuhkan Karakter Religius Siswa Sekolah Dasar Melalui Program Keagamaan - Ramawati, Rizka; Supriyadi, Supriyadi (EduInovasi: Journal of Basic Educational Studies, 2024)
The research objectives to be achieved are to describe the role of the classroom teacher in cultivating the religious character of elementary school students through religious programs and to describe what factors support and hinder the implementation of religious programs in cultivating religious character at Muhammadiyah 1 Krian Elementary School. is a qualitative descriptive method. The subjects in this study were Class V teachers as well (Heads of Islamic affairs). Methods of data collection using the method of observation, interviews, and documentation. The data analysis technique uses interactive analysis with data reduction, data presentation, and conclusion drawing steps. The results of the study show that the role of the classroom teacher in cultivating the religious character of students through religious programs includes the role of the teacher educating students to get used to reading the Koran for 1 hour before learning takes place. Second, the teacher sets an example in carrying out Duha, Dhuhr and Asr prayers in congregation at school. Third, the teacher guides in carrying out the memorization of the Qur'an. The supporting factors in cultivating students' religious character include support from parents, commitment with school members, and adequate facilities. While the inhibiting factors include different student backgrounds, lack of student awareness, and student environment or association. Keywords: Teacher's Role, Religious Character, Religious Program